Alternatif Penanggulangan Bencana Banjir dengan Penerapan Teknologi Biopori di Desa Molingkapoto - Risti Ristianingsih Badu; Wahidin Lukum; M. Rachmat Tahir; Aldy Prasetyo; Intan Nuraini Ibrahim; Fitriyani Yusuf; Sri Ansiska; M. Noval Pratama Putra; Siti Srimeyliza Doe; Ismi Regita Gani; Nurjihan Payuyu; Sahlan Friandi Buako; Aditya Gobel; Nandi Rasid (Abdimas Universal, 2023)
Indonesia is one og the countries with a high precipitation. The high precipitation and lack of water catchment areas resulted in flooding. This community service aims to improve the quality of the environment by applying biopore technology as an alternative to flood control in the Malingkapoto Village area, Kwandang District, North Gorontalo Regency. Biopore technology is not only for flood prevention, but can be used as a composting technology. The result of this service activity is that 30 biopore have been installed at several points prone to the largest puddles of water due to high precipitation. This activity is in accordance with what has been planned, such as: increasing community knowledge and skills in flood management, provide business opportunities for biopore pipes and compost fertilizers, and support the local government of Gorontalo Regency in dealing with environmental problems.